Solving station decision problem in bicycle ad hoc networks. (20th August 2014) - Ouyang, Wen; Yu, Chang Wu; Yu, Kun–Ming; Lin, Ko–Jui; Chang, Hsin–Wen; Hsieh, Hung–Nien; Tai, Lin–Li; Lin, Chung–Han
The sport of biking has gained in popularity recently, leading to public bicycle systems (PBSs) being adopted in many cities and communities around the world. However, developing and designing a successful PBS is challenging. This work proposes a novel problem called station decision problem for bicycle ad hoc networks. The problem is to find the minimum number of bike stations required while satisfying reachability and richness conditions. After that, practical geographic concerns, such as unreachable areas and maximum distances, are considered. Station decision algorithms are provided, with simulations conducted to demonstrate the effectiveness of the methods. Real site data are also plugged in to show the result of the station decision algorithms.